A Report Review: Artificial Intelligence and the Future of Teaching and Learning - Kritandani, Weny; Aryani, Renaningtyas; Rakasiwi, Tetta (Faculty of Education Universitas Negeri Malang, 2024)
This review provides an insightful overview of